Optimization of NMC811 Synthesis via Oxalate Coprecipitation Method for Lithium-Ion Battery Cathode - Angellinnov, Fiona; Subhan, Achmad; Priyono, Bambang; Syahrial, Anne Zulfia (National Research and Innovation Agency (BRIN), 2024)
NMC811 was synthesized through the oxalate coprecipitation method, followed by the solid-state method of lithiation. Stirring speed (500, 750, 1000 rpm), aging time (0, 3, 5h), sintering atmosphere (with and without oxygen flow), sintering temperature (700, 750, 800 °C), and lithium concentration (0, 2, 5% excess) effect on the NMC811 were examined. Characterization results showed that the optimum stirring speed and aging time are 750 rpm and 3 hours. Based on structural analysis, the best condition for sintering is in oxygen atmospheres at 800 °C with a lithium concentration of 2% excess. NMC811, synthesized with these optimum parameters, provided a 212.93 mAh/g capacity. These findings deliver insight into NMC811 synthesis optimization.